HLA class I and class II associations in dengue viral infections in a Sri Lankan population. - Malavige, G; Rostron, T; Rohanachandra, LT; Jayaratne, S; Fernando, N; De Silva, A; Liyanage, M; Ogg, G (Public Library of Science, 2011)
BACKGROUND: HLA class I and class II alleles have been shown to be associated with the development of dengue hemorrhagic fever (DHF)/dengue shock syndrome (DSS) in different populations. However, the majority of studies have been based on limited numbers of patients. In this study we aimed to investigate the HLA-class I and class II alleles that are positively and negatively associated with the development of DSS in a cohort of patients with DHF and also the alleles associated with development of DHF during primary dengue infections in a Sri Lankan population. METHODOLOGY/PRINCIPAL FINDINGS: The allele frequencies of HLA class I and class II alleles were compared in 110 patients with DHF and 119 individuals from the population who had never reported a symptomatic dengue infection at the time of recruitment. We found that HLA-A*31 (corrected P = 0.01) and DRB1*08 (corrected P = 0.009) were associated with susceptibility to DSS when infected with the dengue virus, during secondary dengue infection. The frequency of DRB1*08 allele was 28.7 times higher than in the normal population in patients with DSS. HLA-A*31 allele was increased 16.6 fold in DHF who developed shock when compared to those who did not develop shock. A*24 (corrected P = 0.03) and DRB1*12 (corrected P = 0.041) were strongly associated with the development of DHF during primary dengue infection. CONCLUSIONS/SIGNIFICANCE: These data suggest that certain HLA alleles confer susceptibility/protection to severe dengue infections. As T cell epitope recognition depend on the HLA type of an individual, it would be now important to investigate how epitope specific T cells associate with primary and secondary dengue infections and in severe dengue infections.